Radiological findings in 31 patients with chondroblastoma in tubular and non-tubular bones - Suphaneewan Jaovisidha (2018)
Introduction This study aimed to evaluate radiological findings in patients with chondroblastoma (CB) in tubular and non-tubular bones (NTBs). Methods We retrospectively reviewed the medical records of patients with CB. Data collected included patients' gender and age, type, size and location of bone involved, and imaging findings regarding border, lobulation, calcification, trabeculation, cortical expansion and destruction, periosteal reaction, soft tissue component and fractures. Magnetic resonance imaging and/or multidetector computed tomography were used to determine the presence of any internal cystic space or secondary aneurysmal bone cyst that may have affected the radiological appearance of CB. Results All 31 lesions (18 tubular bones, 13 NTBs) exhibited geographic bone destruction and did not involve the adjacent joints. Univariate analysis showed that NTB lesions were found in older patients and were associated with thin trabeculation (p < 0.01) and well-defined margins (p < 0.05), whereas tubular bone lesions correlated with thick trabeculation and partially ill-defined margins. On multivariate analysis, age and type of bone involvement were significantly correlated. An increase in age by one year reduced the risk of having tubular bone involvement by about 27% when compared with NTBs (p = 0.011). Thin trabeculation was also significantly correlated with NTB lesions. Conclusion Age was the most significant parameter, as increased age was found to reduce the risk of tubular bone involvement. Patients with NTB lesions were significantly older than those with tubular bone lesions. Based on imaging alone, thin trabeculation showed significant correlation with CB occurring in NTBs on both univariate and multivariate analyses.